2005
DOI: 10.1007/s10654-005-1752-x
|View full text |Cite
|
Sign up to set email alerts
|

Marital differences in blood pressure and the risk of hypertension among Polish men

Abstract: The aim of the study was to evaluate the relationship between marital status and blood pressure, and to assess the risk of hypertension in adult Polish men, after adjustment for BMI. Material comprised the data of 2,271 healthy men, aged 25-60, occupationally active inhabitants of Wroclaw (south-western Poland). Arterial hypertension was diagnosed when systolic blood pressure (SBP) > or =140 mm Hg and/or diastolic blood pressure (DBP) > or = 90 mm Hg. The following categories of marital status and educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 38 publications
5
25
4
1
Order By: Relevance
“…The literature highlights a greater chance of hypertension in Blacks. 19 In the present study, the skin color was not associated with hypertension, which was comparable with another study that included this variable in its analyses. 17 This shows that the extension of the impact of the Brazilian miscegenation on hypertension is still unclear.…”
Section: 16supporting
confidence: 89%
“…The literature highlights a greater chance of hypertension in Blacks. 19 In the present study, the skin color was not associated with hypertension, which was comparable with another study that included this variable in its analyses. 17 This shows that the extension of the impact of the Brazilian miscegenation on hypertension is still unclear.…”
Section: 16supporting
confidence: 89%
“…However, in middle-income countries, the results diverged: married men, when compared with their unmarried counterparts, had a higher risk of hypertension in Barbados35 and a lower risk in Poland 63. Married individuals had higher emotional and social support and lower stress63 and the probability of being a current smoker 64. We found that incident hypertension was relatively more frequent among married women, unlike the no-sex-link pattern in developed countries such as the USA and Korea 53 54.…”
Section: Discussionmentioning
confidence: 98%
“…However, in middle-income countries, the results diverged: married men, when compared with their unmarried counterparts, had a higher risk of hypertension in Barbados35 and a lower risk in Poland 63. Married individuals had higher emotional and social support and lower stress63 and the probability of being a current smoker 64.…”
Section: Discussionmentioning
confidence: 99%
“…Additional clinical and socioeconomic factors were selected if considered to be potential confounders of the relationship between dysglycemia and hypertension. For instance, prior studies have suggested that breastfeeding results in lower maternal blood pressure; 17 marriage is associated with a lower risk of hypertension; 18 smoking is a significant independent risk factor for hypertension; 19 and education is inversely associated with hypertension risk factors, such as smoking, BMI, and systolic blood pressure. 20 …”
Section: Methodsmentioning
confidence: 99%